The competence of managers in growing the business of cooperatives in Pangandaran Regency, West Java Province Indonesia - Abdul Muhyi, Herwan; Sukoco, Iwan (International Journal of Engineering and Technology, 2018)
The aim of this research was to find information relating to managers competencies of cooperatives in Pangandaran Regency and to compare the condition to the theory proposed by Spencer and Spencer (1993) to discover the extent of managers competencies of cooperatives in Pangandaran Regency. This research applied the qualitative method with the researcher as the instrument of research. Data were obtained from informants selected according to the need and purpose of the research or in another case it is called purposive sampling. Data collection was conducted through observation, literature review, in-depth interviews, and focus group discussion and subsequently data was analyzed by making reduction, presentation, conclusion, and verification. The research result indicated that regarding competencies the majority of managers of cooperatives in Pangandaran Regency have not yet been skillful in handling managerial aspects and techniques for managing cooperatives. It attracted the attention of the local government to participate in enhancing human resources of cooperatives; hence the government provided training assistance which has been conducted several times since the establishment of cooperatives in Pangandaran Regency. However, the enhancement of human resources competencies has not yet showed a significant result. The explanation above provides a conclusion that up to now managers competencies of cooperatives in Pangandaran Regency still need enhancement through training and provisioning of managerial and technical aspects.Â